'n kritiese beskouing van die rol en funksies van die gemeenskapsgesondheids verpleegkundige in groot stedelike plaaslike owerheidsdienste in die Republiek van Suid-Afrika - Johanna M. Dreyer (AOSIS, 1989)
The aim o f this study was to determine and describe the role and functions o f the community health nurse in the health services o f local authorities o f the larger cities within the framework o f legislation regarding health and the health service structure o f the Republic o f South Africa. A questionnaire was used to gather data in connection with the present role and functions o f the community health nurse who is responsible fo r direct client I patient care in the local authority areas o f Greater Cape Town, Port Elizabeth, Durban, Pretoria, Johannesburg and Bloemfontein. The information gained from the questionnaires was followed up by personal observations o f the services tendered in Greater Cape Town, Durban and Johannesburg, after it had been computed. The study indicates that the community health nurse in the urban, local authority health services o f the Republic makes a very important contribution to the delivery o f services within the provisions o f the Health Act, no. 63 of 1977. The analysis o f the computed data and personal observations showed that the community health nurse in the large cities must carry out a certain percentage o f the administrative, educational, preventive, promotive, curative and rehabilitative activities in the services.